2011
DOI: 10.1038/ki.2011.47
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 is elevated before parathyroid hormone and phosphate in chronic kidney disease

Abstract: Fibroblast growth factor 23 (FGF23) regulates phosphorus metabolism and is a strong predictor of mortality in dialysis patients. FGF23 has been proposed as an early biomarker of disordered phosphorus metabolism in earlier stages of chronic kidney disease (CKD), but data from large, well-characterized CKD cohorts are lacking. We measured FGF23 in baseline samples from 3,879 participants in the Chronic Renal Insufficiency Cohort study, a nationally representative, diverse CKD cohort with mean (± sd) estimated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
876
7
31

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,072 publications
(981 citation statements)
references
References 49 publications
39
876
7
31
Order By: Relevance
“…Other mechanisms by which FGF‐23 could lead to adverse cardiovascular consequences include calcitriol deficiency, altered phosphorus homeostasis, systemic inflammation and oxidative stress, and sodium retention 31, 32, 33. Additionally, FGF‐23 may downregulate soluble α‐klotho,34 an enzyme with anti‐aging effects that was shown to protect the heart against cardiac hypertrophy and cardiac remodeling 35, 36. In a study by Reindl et al, FGF‐23 was significantly higher in patients who developed LV remodeling post ST‐segment–elevation myocardial infarction even after adjustment for biomarkers of myocardial necrosis, myocardial stress, and inflammation 37.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms by which FGF‐23 could lead to adverse cardiovascular consequences include calcitriol deficiency, altered phosphorus homeostasis, systemic inflammation and oxidative stress, and sodium retention 31, 32, 33. Additionally, FGF‐23 may downregulate soluble α‐klotho,34 an enzyme with anti‐aging effects that was shown to protect the heart against cardiac hypertrophy and cardiac remodeling 35, 36. In a study by Reindl et al, FGF‐23 was significantly higher in patients who developed LV remodeling post ST‐segment–elevation myocardial infarction even after adjustment for biomarkers of myocardial necrosis, myocardial stress, and inflammation 37.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually failing allografts lead to post-transplantation CKD stage 3-5 leading to increased risk of worsening or de novo development of hyperparathyroidism with active vitamin D deficiency and metabolic disorders similar to those observed before transplantation (22).…”
Section: Chronic Allograft Nephropathymentioning
confidence: 99%
“…Previous studies in adult and pediatric patients have demonstrated that FGF-23 levels are elevated in early CKD and increase with CKD progression, suggesting that renal injury affects the skeleton in even very early stages of CKD (7)(8)(9). However, the skeletal changes associated with circulating FGF-23 levels in predialysis CKD are unknown, and it remains uncertain whether FGF-23 levels increase before PTH elevations become detectable or whether an increase in PTH, which has been shown in some studies to increase FGF-23 levels (10), precedes the increase in FGF-23.…”
Section: Introductionmentioning
confidence: 99%